Dream chasers - "Mitra, Vipul" (Noida, 2013)
Six friends at university are pursuing the coveted MBA. Viraat, Sandy, Karan, Mallika, Vandana and Preeto are a gang who hang out together and get into trouble together. And when the boys are not in their classrooms, they're indulging in some high octane fun-from experimenting with dope, riding bikes semi-naked to even sneaking into cabarets. To add to their complicity, they are all vying for the attention of the same girl- Mallika. As their term ends, a disillusioned Viraat discovers that his gang that was once inseparable has disintegrated and his wild, carefree days are now history. His past catches up with him faster than he excepts and he is left in the biggest rut of his life. Will Viraat get past the hurdles to pave a path of his own? Will he finally get Mallika, the girl of his dreams? Most importantly, are his dreams even worth chasing? The Dream Chasers is a hysterical and candid story about fate, love and the follies of youth.
Keywords: Fiction